Health professionals' subjectivation towards end of life and death in home care service - Jéssica Siqueira Perboni; Stefanie Griebeler Oliveira; Franciele Roberta Cordeiro (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the modes of subjectification of health professionals towards end of life and death in a home care service. Methods: this is qualitative research carried out in a home care service at a teaching hospital in southern Brazil, with 12 health professionals. Participant observation and semi-structured interviews were used for data collection, from April to September 2018. Data were analyzed based on Foucault's concept of power and subjectivation. Results: professionals are sensitized by moral, spiritual and palliative care discourses, as well as experiences that constitute them subjects who modify their ways of life and professional practice based on the relation with death. Final Considerations: the discursive network of palliative care is internalized by professionals, who carry out their practices with behaviors aimed at promoting "a good death".